Working Relationally with Networks of Support Within Schools: Supporting Teachers in their Work with Shy Students. Issue 4 (2nd October 2021) - Solberg, Stine; Edwards, Anne; Mjelve, Liv Heidi; Nyborg, Geir
Abstract: Childhood shyness and associated psychosocial difficulties can place pupils at risk of underperforming cognitively. Yet shyness is not regarded as a special need demanding a response from education professionals. In this article, drawing on data from a national study of how teachers support shy children, we trace how teachers negotiate this support from the networks of teachers and carers that are available to them. Data comprised post-observation recall interviews, individual interviews and focus groups with teachers, all of whom had successful experiences with shy students. Qualitative responses from a national teacher survey were also analyzed. Analyses were guided by three cultural-historical concepts which explain professional relationships. Four networks were identified: teacher teams; school resource teams; school leadership teams and families. With peers the negotiation was horizontal, drawing on shared concerns with children as learners; with resource teams teachers negotiated upwards by recognizing and addressing the priorities of the resource teams; with leadership teams the school Principals worked relationally and pedagogically with teachers to enable their agentic responses to challenges; while with families teachers worked sensitively to elicit the what mattered for the families and encourage relational collaborations with school professionals. The implications for professional learning and school leadership are discussed.